Detection of Oil Mineral Pollution in Tigris River from Aldora Refined using Absorbance Spectroscopy - Mohammed, Thamer Mahmood; Ahmed, Ahmed K. (Al-Nahrain Journal for Engineering Sciences, 2024)
Accurately identifying the kind and amount of dissolved metal salts in wastewater used in oil refining processes is an iconic feature of ultraviolet and visible absorption spectroscopy. This method relies on the dissolved metal salts' ability to absorb light at certain wavelengths after reacting with it. The experiments were conducted in a lab setting with a broadband source (200-800 nm) to measure the absorbance of dissolved element salts and precisely identify the lowest concentration up to 2 ppm. A mixture of the mineral salts from oil refining operations was prepared and diluted to different concentrations using a standard solution. This allowed us to study and compare this result with the absorbance behavior of the wastewater from the Al-Dora Refinery. The two results reinforced that we can accurately estimate the detection parameters for the lowest water contamination. These materials are lead nitrate (PbNO3), phenol, calcium carbonate (CaCO3), sodium chloride (NaCl2), sulfide (SO4), and nitrate (NO3). At wavelengths of 340, 404, and 741 nm, the concentrations (10, 20, 30, 40, 50, 60, 70, 80, 90, and 100) ppm were found, and for the concentration of 10ppm, the absorbance (0.15323, 0.15326, and 0.14685) was found, respectively. The process that has been tested with varying concentrations is considered and simulates the variation in river water concentrations caused by the river's water level and flow rate changes by the effect of rain abundance and thawing. It is fast, accurate data analysis, and a lower cost compared with the other chemical analysis and conventional methods.